Decisions to Replace Consumer Durables Goods: An Econometric Application of Wiener and Renewal Processes - Fernandez, Viviana P. (The Review of Economics and Statistics, 2000)
Current sales of most consumer durable goods are accounted for by replacements. However, only in recent years has the economic literature provided a more rigorous analysis of replacement purchases by incorporating elements of dynamic programming and of the theory of stochastic processes. This paper is an empirical study of household replacement decisions modeled as an optimal stopping rule. Using data from the Residential Energy Consumption Survey (RECS) of the U.S. Department of Energy, we conclude that demographic variables, operation and replacement costs, and equipment characteristics may affect ownership spells of appliances such as electric heaters and central air conditioners.